Combinatorial Application of Papain and CD66B for Isolating Glioma- Associated Neutrophils - Xu, Xing; Yang, Yongchang; Liu, Yancheng; Ge, Xianglian; Yi, Tailong; Xie, Yang; Ning, Chunlan; Shen, Shengfu; Sun, Zengfeng; Zhang, Zhen; Zhai, Qiongli; Wang, Xiaoguang; et al. (Current Cancer Drug Targets, 2023)
Background: Stromal cells in the tumor microenvironment play crucial roles in glioma development. Current methods for isolating tumor-associated stromal cells (such as neutrophils) are inefficient due to the conflict between tissue dissociation and cell surface protein protection, which hampers the research on patient-derived stromal cells. Our study aims to establish a novel method for isolating glioma-associated neutrophils (GANs). Methods: To observe neutrophil-like polymorphonuclear cells, we performed Hematoxylin-Eosin staining on glioma tissues. For isolating single cells from glioma tissues, we evaluated the efficiency of tissue dissociation with FastPrep Grinder-mediated homogenization or proteases (trypsin or papain) digestion. To definite specific markers of GANs, fluorescence-activated cell sorting (FACS) and immunofluorescence staining were performed. FACS and Ficoll were performed for the separation of neutrophils from glioma tissue-derived single-cell or whole blood pool. To identify the isolated neutrophils, FACS and RT-PCR were carried out. Results: Neutrophil-like cells were abundant in high-grade glioma tissues. Among the three tissue dissociation methods, papain digestion produced a 5.1-fold and 1.7-fold more living cells from glioma mass than physical trituration and trypsin digestion, respectively, and it preserved over 97% of neutrophil surface protein markers. CD66B could be adopted as a unique neutrophil surface protein marker for FACS sorting in glioma. Glioma-derived CD66B+ cells specifically expressed neutrophil marker genes. Conclusion: A combination of papain-mediated tissue dissociation and CD66B-mediated FACS sorting is an effective novel method for the isolation of GANs from glioma tissues.
Keywords: Glioblastoma